1993
DOI: 10.1007/bf00979660
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active secondary metabolites of barley. II. Phytotoxicity of barley allelochemicals

Abstract: The release of alkaloids by barley was quantified by HPLC. Hordenine was released from the roots of barley in a hydroponic system for up to 60 days. The amount reached a maximum, 2μg/plant/day, at 36 days, then declined. Effects on white mustard by hordenine and gramine included reduction of radicle length and apparent reduction in health and vigor of radicle tips. Transmission electron microscopic examination of white mustard radicle tips exposed to hordenine and gramine showed damage to cell walls, increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 23 publications
4
53
1
3
Order By: Relevance
“…Indeed, there is an increasing interest in the weed suppressive ability of crops for both organic and conventional farming systems (Mason and Spaner 2006). Cereal crop plants, such as wheat (Lodhi et al 1987;Wu et al 2000a, b), barley (Overland 1966;Liu and Lovett 1993b;Fujii 2001) and rice (Olofsdotter et al 1999), have been shown to produce allelochemicals with a capacity to reduce growth of other plant species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is an increasing interest in the weed suppressive ability of crops for both organic and conventional farming systems (Mason and Spaner 2006). Cereal crop plants, such as wheat (Lodhi et al 1987;Wu et al 2000a, b), barley (Overland 1966;Liu and Lovett 1993b;Fujii 2001) and rice (Olofsdotter et al 1999), have been shown to produce allelochemicals with a capacity to reduce growth of other plant species.…”
Section: Introductionmentioning
confidence: 99%
“…have been identified as potential allelochemicals that contribute to the allelopathic effectiveness of barley (Kremer and Ben-Hammouda 2009). The two alkaloids, gramine and hordenine, were the first allelochemicals proposed to explain the allelopathic effects of barley (Overland 1966;Liu and Lovett 1993b).…”
Section: Introductionmentioning
confidence: 99%
“…The leaf area results show that in the extract regime, the leaf area of the seedlings was higher than in those of seedlings in water regime, except again for D. guineense, where that of water regime was a little more than that of of other plants, including the growth of several crops (Oyerinde et al, 2009), and most times, it completely suppress other plants that share the same habitat (Liu and Lovett, 1993). The allelopathic interactions between plants have been implicated in the patterning of vegetation and weed growth in agricultural systems (Rice, 1984).…”
Section: Tenuifolia and H Barteri But It Was Inhibitory In Dmentioning
confidence: 98%
“…In the studies of biologically active secondary metabolites of barley alkaloids, Liu and Lovett (1993) found that a concentration of hordenine at 48 ppm can cause a substantial response in the form of increases in number and size of vacuoles and seriously damaged cell walls in the root tips of white mustard. Using CARD, it attains that this concentration (48 ppm hordenine) used to treat the root tips of white mustard causes 18% of reduction in radicle length.…”
Section: Figurementioning
confidence: 99%